DINAMIKA PENYELESAIAN SENGKETA LINGKUNGAN HIDUP DI INDONESIA - Selamet Suhartono (Widya Yuridika, 2018)
Any solution to the environment in Indonesia is very dynamic in line with the development: UULH (the law on the environment) was regulated through the court channel and tripartite institutions, UUPLH (the law on the environmental management), through the court and out of cour channels, namely the institution with an authotiry to decide and not to decide but the forms of the institutions are not clearly mentioned, namely arbitration and mediation which is clearly stated. The use of the court channels is based on the choices made by parties, and it is marely solved through the court if this kind of solution is stated to be wrong by one two parties.Kata Kunci: sengketa lingkungan, pengadilan, luar pengadilan.